Protective Effects of Adeno-associated Virus Mediated Brain-derived Neurotrophic Factor Expression on Retinal Ganglion Cells in Diabetic Rats - Gong, Yan; Chang, Zhan-Ping; Ren, Ruo-Tong; Wei, Shi-hui; Zhou, Huan-Fen; Chen, Xiao-fei; Hou, Bao-ke; Jin, Xin; Zhang, Mao-nian (Cellular and molecular neurobiology, 2012)
Adeno-associated virus vector plasmid carrying the expression cassette of brain-derived neurotrophic factor (BDNF), pAAV-BDNF, was constructed and packaged into recombinant adeno-associated virus (rAAV-BDNF). The rAAV-BDNF was intravitreally injected into streptzotocin (STZ)-induced diabetic Sprague–Dawley (SD) Rats. Data showed that over-expression of BDNF could increase alive retinal ganglion cell (RGC) number and improve its function in streptzotocin(STZ)-induced diabetic rats, which might be a new method to treat diabetic neuropathy andretinopathy.